2009
DOI: 10.1007/s12020-009-9281-0
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of lymphomononuclear cell energy metabolism between healthy, impaired glucose intolerance and type 2 diabetes mellitus patients

Abstract: Diabetes mellitus (DM) is a complex disease that affects many systems. The most important cells of the immune system are lymphomononuclear (LMN) cells. Here, we aimed to evaluate the energy metabolism of LMN cells in patients with diabetes and impaired glucose tolerance. We measured LMN cell energy metabolism in patients with type 2 diabetes mellitus, impaired glucose tolerance (IGT) and healthy subjects. Cells were freshly isolated from peripheral blood and the subgroups were determined by flow cytometric met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
6
1
Order By: Relevance
“…Chronic and persistent calcium entry into the cell occurs and leads to inhibition of mitochondrial oxidation and reduction in the amount of ATP [2][3][4][5]. Deterioration in the energy metabolism of immune system plays a crucial role in the development of infections [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic and persistent calcium entry into the cell occurs and leads to inhibition of mitochondrial oxidation and reduction in the amount of ATP [2][3][4][5]. Deterioration in the energy metabolism of immune system plays a crucial role in the development of infections [6].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic patients are known to be susceptible to infections. One of the reasons for this increased susceptibility to infections may be a decrease in the oxidative mechanism, a decrease in the nonoxidative mechanism, or a decrease in both mechanisms compared to healthy volunteers [6].…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral blood mononuclear cell (PBMC) energy metabolism has been found to play a major role in the pathogenesis of insulin resistance [30]. In addition, there is increasing evidence that metabolic regulation in these cells could influence the number of PBMCs, proliferation pathways, molecular basal synthesis and leukocyte function [31]. In accordance with these findings, transcriptome studies comparing T1D with T2D [32] and T1D with a control group [18] have revealed changes in the expression of several genes related to inflammatory response, fatty acid biosynthesis, hydrolase activity, detoxification of aldehydes generated by alcohol metabolism and lipid peroxidation, all of which could affect the metabolism of PBMCs in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the these factors, it is also shown that in prediabetic state per se, the lymphomononuclear (LMN) cells change their energy pathway leading to anaerobic glycolysis and this abnormal energy production might cause dysfunction in LMN cells and the immune system in diabetic and prediabetic patients [46]. Furthermore, an association of Hepatitis C virus with insulin resistance among adults was observed and abnormal glucose tolerance was found to be more common in HCV-seropositive individuals than seronegative individuals among obese participants suggesting that it could be an additional risk factor in the impairment of immune function of WNIN/GR-Ob obese rats [47].…”
Section: Discussionmentioning
confidence: 99%